Penerapan Model Pembelajaran Kooperatif Tipe Teams Game Tournament (TGT) untuk Meningkatkan Minat Belajar PKn - ni nyoman sukasih (Universitas Pendidikan Ganesha, 2018)
This research aimed at implementing cooperative learning type Teams Game Tournament (TGT) to improve students’ learning interest in civic education. The subjects of this classroom action research were 26 students in Grade V, semester II, academic year 2015/2016 in SD No.1 Darmasaba. Students’ interests were collected using observation sheet and analyzed descriptively. Result showed that the implementation of cooperative learning type TGT could improve students’ interest in civic education. Students’ interests were increase from 16 after Cycle I to 20 after Cycle II. Students’ classical completeness was also increase from 77% after Cycle I to 100% after Cycle II.